Federalism and fiscal balance : a comparative study - Hunter, J. S. H. (Canberra : Australian National University Press, 1977)
It looks at the growing signs that the federal structure in Australia is in jeopardy and that some fairly fundamental changes in fiscal arrangements are needed to retrieve the situation.
Includes bibliographical references: p. [256]-265 and index.
oif 03/06/2019
Loans
Keywords: Intergovernmental fiscal relations; Federal government